Bladder cancer, a review of the environmental risk factors - Letašiová Silvia; Medveďová Alžbeta; Šovčíková Andrea; Dušinská Mária; Volkovová Katarína; Mosoiu Claudia; Bartonová Alena (BMC, 2012)
Abstract Background Many epidemiological studies and reviews have been performed to identify the causes of bladder cancer. The aim of this review is to investigate the links between various environmental risk factors and cancer of the bladder. Methods A systematic literature search was performed using PubMed, Science Direct, Scopus, Scholar Google and Russian Google databases to identify reviews and epidemiological studies on bladder cancer risk factors associated with the environment published between 1998 and 2010. Only literature discussing human studies was considered. Results Smoking, mainly cigarette smoking, is a well known risk factor for various diseases, including bladder cancer. Another factor strongly associated with bladder cancer is exposure to arsenic in drinking water at concentrations higher than 300 µg/l. The most notable risk factor for development of bladder cancer is occupational exposure to aromatic amines (2-naphthylamine, 4-aminobiphenyl and benzidine) and 4,4'-methylenebis(2-chloroaniline), which can be found in the products of the chemical, dye and rubber industries as well as in hair dyes, paints, fungicides, cigarette smoke, plastics, metals and motor vehicle exhaust. There are also data suggesting an effect from of other types of smoking besides cigarettes (cigar, pipe, Egyptian waterpipe, smokeless tobacco and environmental tobacco smoking), and other sources of arsenic exposure such as air, food, occupational hazards, and tobacco. Other studies show that hairdressers and barbers with occupational exposure to hair dyes experience enhanced risk of bladder cancer. For example, a study related to personal use of hair dyes demonstrates an elevated bladder cancer risk for people who used permanent hair dyes at least once a month, for one year or longer. Conclusion Smoking, in particular from cigarettes, exposure to arsenic in drinking water, and occupational exposure to aromatic amines and 4,4'-methylenebis(2-chloroaniline) are well known risk factors for various diseases including bladder cancer. Although the number of chemicals related to occupational exposure is still growing, it is worth noting that it may take several years or decades between exposure and the subsequent cancer.